A Mitigation Technique for Inrush Currents in Load Transformers for the Series Voltage Sag Compensator - Prasad, Besta Hari; Reddy, Poreddy Harshavardhan; Lalitha, M. Padma (International Journal of Intelligent Systems and Applications in Engineering, 2014)
In many countries, high-tech manufacturers concentrate in industry parks. Survey results suggest that 92% of interruption at industrial facilities is voltage sag related. An inrush mitigation technique is proposed and implemented in a synchronous reference frame sag compensator controller. The voltage sag compensator consists of a three phase voltage source inverter and a coupling transformer for serial connection. It is the most cost effective solution against voltage sags. When voltage sag happen, the transformers, which are often installed in front of critical loads for electrical isolation, are exposed to the disfigured voltages and a DC offset will occur in its flux linkage. When the compensator restores the load voltage, the flux linkage will be driven to the level of magnetic saturation and severe inrush current occurs. The compensator is likely to be interrupted because of its own over current protection. This paper proposes an inrush current mitigation technique together with a state-feedback controller for the Voltage sag compensator.